Data and code for "Hydrogen-driven Surface Segregation in Pd-alloys from Atomic Scale Simulations" - Ekborg-Tanner, Pernilla; Erhart, Paul (Chalmers University of Technology, 2021)
This record contains data and scripts pertaining to the publication "Hydrogen-driven Surface Segregation in Pd-alloys from Atomic Scale Simulations".
Keywords: Physical Sciences; Fysik